Report of the Workshop Predictive Theoretical, Computational and Experimental Approaches for Additive Manufacturing (WAM 2016) - Guo, Xu.; Cheng, Gengdong; Liu, Wing-Kam.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The volume focuses on theoretical and computational approaches and involves areas such as simulation-based engineering and science, integrated computational materials engineering, mechanics, material science, manufacturing processes, and other specialized areas. Most importantly, the state-of-the-art progress in developing predictive theoretical, computational and experimental approaches for additive manufacturing is summarized.
Introduction -- Theoretical understanding of material science and mechanics in additive manufacturing -- Computational and analytical methods in additive manufacturing. - Theory, methods and tools for additive manufacturing oriented design and optimization -- Additive manufacturing experimental methods and results, and additive manufacturing scalability. summary of group discussions -- References.
Keywords: Manufactures; Engineering mathematics; Engineering -- Data processing; Machines, Tools, Processes; Mathematical and Computational Engineering Applications